SEBARAN BENTENG DI KABUPATEN BUTON TENGAH PROVINSI SULAWESI TENGGARA - Ade Trie Yunizar; sitti kasmiati; sandy suseno (SANGIA: Jurnal Penelitian Arkeologi, 2018)
This study aimed to discover and describe the remaining archeology which is a fortress at central Butondistrict, the spread of the fortress that exist and factors affects the spread of the fortress. This study usedinductive reasoning method which is a study based on observation until the conclusion with technique ofcollecting the data which consisted of observation, interview, and literature review, and data analysis used spatialand contextual analysis.The result showed that at central Buton district there was remaining archeology which isa spread fortress that formed a four spread of fortress. The spread I consisted of a fortress built in group in thesame area meanwhile spread II, III and IV were built in three different areas. The construction of fortresses wasaffected from few factors that were physical environmental factosuch as topography, altitude, soil type and goodhydrology gave the construction of the fortress at ease, and could fulfill the needs of the people who live in thefortress and facilitate the safety if natural disasters occur.Then the other environmental factors were the locationof the fortress which in general was located in thecoastal area, though it was located in the hilly area but thelocation of the fortress could monitor territorial waters.